Socio-cultural principles of the concept of "living law" Eugene Ehrlich - Podkovenko, Tetiana; Chorna, Kateryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The article analyzes Ehrlich’s innovative approach to understanding law. Today we can state with sufficient grounds that E. Ehrlich thought of law as a socio-cultural, spiritual in nature, created by the joint efforts of society. E. Ehrlich was one of those thinkers who in the era of the dominance of legal-positivist methodology defended the principle of pluralism in views on the origins of law, truth in law, the methodology of its study. According to Ehrlich, law appears as a living, complex, multifaceted phenomenon that is closely connected with life circumstances, determined by them, accumulates a rich world of human culture.